Efforts to Improve Scientific Thinking Skills Through Application Discovery Model-Based Learning Environment Around - Rindang Prakasiwi; Bambang Ismanto (Journal of Educational Science and Technology (EST), 2018)
The purpose of the study was to describe the steps of the Discovery Learning-based learning model that can improve students' scientific thinking skills and to find out the effect of the Discovery Learning learning model on improving scientific thinking skills of first grade elementary school(Blotongan 02) students in thematic learning of two subjects: Indonesian and Mathematics. This is a classroom action research conducted in 2 cycles. The instruments used in data collection were questions, observation sheets, questionnaires, and documentation. Qualitative analysis technique was conducted on the data of scientific thinking skills while the quantitative analysis was conducted on the data of learning mastery. The results of the research show that in the first cycle, the students’ mean score was 2.60 (good) and increased to 3.28 (very good) in cycle II. In the first cycle, 67% of students completed the minimum standard and in the second cycle, it increased to 85%. Thus, thematic learning using the Discovery Learning model based on the surrounding environment was concluded to improve scientific thinking skills and learning completeness of students in grade 1, SD Negeri Blotongan 02.